O konieczności redefinicji pojęcia suwerenności w kontekście integracji europejskiej - Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Today, the bare existence of sovereign states in Europe is questioned in terms of agiven definition. Regarding the members of the European Union, changes in sovereignty are found to be significant by many. The member states have transferred agreat share of their competencies to the European Union by means of founding treaties, so they cannot freely regulate awide variety of issues which used to be under exclusive jurisdiction of the states. This article analyses contemporary legal theories which discuss sovereignty in accordance with the new development trends and is aimed at dealing with the issue of the future of the sovereignty concept. Its intention is to show that those challenges represent aserious threat to the sovereignty concept which is still worth defending and supporting. Though its nature is being changed, sovereignty does not disappear.
Keywords: integracja europejska; suwerenność; redefinicja pojęcia